A companion to the preclinical common data elements for phenotyping seizures and epilepsy in rodent models. A report of the TASK3‐WG1C: Phenotyping working group of the ILAE/AES joint translational task force - Barker‐Haliski, Melissa; Pitsch, Julika; Galanopoulou, Aristea S.; Köhling, Rüdiger (Epilepsia open, 2025)
Epilepsy is a heterogeneous disorder characterized by spontaneous seizures and behavioral comorbidities. The underlying mechanisms of seizures and epilepsy across various syndromes lead to diverse clinical presentation and features. Similarly, animal models of epilepsy arise from numerous dissimilar inciting events. Preclinical seizure and epilepsy models can be evoked through many different protocols, leaving the phenotypic reporting subject to diverse interpretations. Serendipity can also play an outsized role in uncovering novel drivers of seizures or epilepsy, with some investigators even stumbling into epilepsy research because of a new genetic cross or unintentional drug effect. The heightened emphasis on rigor and reproducibility in preclinical research, including that which is conducted for epilepsy, underscores the need for standardized phenotyping strategies. To address this goal as part of the TASK3‐WG1C Working Group of the International League Against Epilepsy (ILAE)/American Epilepsy Society (AES) Joint Translational Task Force, we developed a case report form (CRF) to describe the common data elements (CDEs) necessary for the phenotyping of seizure‐like behaviors in rodents. This companion manuscript describes the use of the proposed CDEs and CRF for the visual, behavioral phenotyping of seizure‐like behaviors. These phenotyping CDEs and accompanying CRF can be used in parallel with video‐electroencephalography (EEG) studies or as a first visual screen to determine whether a model manifests seizure‐like behaviors before utilizing more specialized diagnostic tests, like video‐EEG. Systematic logging of seizure‐like behaviors may help identify models that could benefit from more specialized diagnostic tests to determine whether these are epileptic seizures, such as video‐EEG.